Treatment outcomes of micropulse transscleral cyclophotocoagulation in advanced glaucoma. Issue 2 (February 2016) - Kuchar, Sarah; Moster, Marlene; Reamer, Courtney; Waisbourd, Michael
Abstract Glaucoma is the leading cause of irreversible blindness worldwide. The goal of this study was to describe our experience with the novel micropulse transscleral cyclophotocoagulation (MP-TSCPC; IRIDEX IQ810 Laser Systems, CA) in patients with advanced glaucoma. Patients with advanced glaucoma who underwent MP-TSCPC were included in our study. Laser settings were 2000 mW of 810 nm infrared diode laser set on micropulse delivery mode. The laser was delivered over 360° for 100–240 s. The duty cycle was 31.3 %, which translated to 0.5 ms of "on time" and 1.1 ms of "off time." Surgical success was defined as an intraocular pressure (IOP) of 6–21 mmHg or a reduction of IOP by 20 % at the last follow-up visit. Failure was defined as an inability to meet the criteria for success or a need for incisional glaucoma surgery. Nineteen patients underwent MP-TSCPC with mean follow-up of 60.3 days. Mean IOP dropped from 37.9 mmHg preoperatively to 22.7 mmHg at last follow-up, representing a 40.1 % decrease. The success rate for initial treatment was 73.7 % (n  = 14). Three patients underwent a second treatment, increasing the overall success rate to 89.5 % (n  = 17). Four patients gained one line of vision, and four patients lost one line of vision. The novel MP-TSCPC laser had a high rate of surgical success after a short follow-up period in patients with advanced glaucoma. Further long-term evaluation and comparison to the traditional transscleral cyclophotocoagulation are warranted.